Update on Changing Terminologies in Sepsis - Simalti, Ashish Kumar; Ghuliani, Ranjit; Nair, Bindu T. (Journal of Nepal Paediatric Society, 2016)
Definitions of sepsis and septic shock were last revised in 2001. Since then there have been considerable advances in our understanding of pathophysiology, management, and epidemiology of sepsis, suggesting the need for reexamination. The European Society of Intensive Care Medicine and the Society of Critical Care Medicine convened a task force in January 2014 with objective to evaluate and, as needed, update definitions for sepsis and septic shock. Recommendations of this task force were published recently as “The Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3)”. The aim of this article is to generate awareness and discussion regarding this new important development.